1990
DOI: 10.1128/jb.172.10.5555-5562.1990
|View full text |Cite
|
Sign up to set email alerts
|

Trigger factor depletion or overproduction causes defective cell division but does not block protein export

Abstract: Trigger factor is an abundant cytosolic protein of Escherichia coli which can stabilize proOmpA for in vitro translocation across inner membrane vesicles. The gene encoding E. coli trigger factor was isolated and sequenced, allowing construction of strains in which the expression of trigger factor is readily regulated. We found no defect in the in vivo rate of synthesis or secretion of proOmpA in trigger factor-depleted cells. The primary physiological defect in trigger factor-depleted or -overproducing cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
103
0
3

Year Published

1995
1995
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(113 citation statements)
references
References 36 publications
7
103
0
3
Order By: Relevance
“…factor fragment The complete rig gene [4] was amplified by PCR using the chromosomal DNA of the E. coli K12 strain DH5a and two primers corresponding to the 5' and 3' regions of the tig gene (5'-CAGTG-GATCCCCATGCAAGTTTCAGTTGAAACC-3' and 5'-CCTGGCGTCGACGGGCCTTTGTGCG-3'). The resulting PCR product was ligated into vector pUC18 and transformed into E. coli strain K12 DH5a.…”
Section: Molecular Cloning Overexpression and Isolation Of The Triggermentioning
confidence: 99%
See 1 more Smart Citation
“…factor fragment The complete rig gene [4] was amplified by PCR using the chromosomal DNA of the E. coli K12 strain DH5a and two primers corresponding to the 5' and 3' regions of the tig gene (5'-CAGTG-GATCCCCATGCAAGTTTCAGTTGAAACC-3' and 5'-CCTGGCGTCGACGGGCCTTTGTGCG-3'). The resulting PCR product was ligated into vector pUC18 and transformed into E. coli strain K12 DH5a.…”
Section: Molecular Cloning Overexpression and Isolation Of The Triggermentioning
confidence: 99%
“…Therefore, stoichiometric complexes of TF and proOmpA could be isolated [2,3]. Using genetically engineered strains of E. coli either over-or underproducing TF, however, the membrane transport of proOmpA was not affected [4]. Further, TF was detected at the 70S ribosome dissociating in a saltdependent manner [5].…”
Section: Introductionmentioning
confidence: 99%
“…When FtsZ is in moderate excess, polar septa are formed, giving rise to minicells Garrido et al, 1993). Moderate overproduction of FtsZ relieves the division inhibition caused by high levels of the division inhibitor SulA (Lutkenhaus et al, 1986), the division inhibitor MinCD (Bi and Lutkenhaus, 1990;Wang et al, 1991) or the trigger factor (Guthrie and Wickner, 1990), as well as that observed in the absence of the molecular chaperone DnaK (Bukau and Walker, 1989). At high FtsZ concentrations, cell division is completely blocked .…”
Section: Introductionmentioning
confidence: 99%
“…At conditions depleting trigger factor to less than 5% of the normal levels, cells remain fully viable but form filaments indicative of cell division defects. No defects in the translocation of proOmpA, even in a trigger factor depletion strain with an additional deficiency for the secretion specific SecB chaperone, were observed [4]. These results suggest that trigger factor is dispensable for growth of E. coli, although analysis of a rig *Corresponding author.…”
Section: Genetic Analysismentioning
confidence: 95%
“…The tig gene encoding trigger factor was cloned [4] and its expression found to be growth phase controlled and thus coregulated with genes encoding ribosomal components (F. Neidhardt, personal communication cited in [4]). Genetic analysis of the in vivo function of trigger factor using a conditional depletion strain failed to provide new insights.…”
Section: Genetic Analysismentioning
confidence: 99%